Late-onset intrascleral dissemination of Pseudomonas aeruginosa scleritis following pterygium excision - Ausayakhun, Somsanguan; Tangmonkongvoragul, Chulaluck; Chaidaroon, Winai; Tananuvat, Napaporn; Niparugs, Muanploy; Supalaset, Sumet (Biomedical Sciences and Clinical Medicine, 2018)
Objective To report on two cases of late-onset intrascleral dissemination of Pseudomonas aeruginosa scleritis following pterygium excision. Methods Case reports. Results Two women, one 67 years old, the second 74 years old, were referred to Chiang Mai University Hospital for treatment of Pseudomonas aeruginosa scleritis 5 years after pterygium excision. In both cases, after admission appropriate antibiotics were extensively administered, both topically and systematically. That therapy was combined with surgical debridement in the second case. After being admitted for 20 and 48 days, the patients’ best corrected visual acuity were 6/6-2, and 6/18+2, respectively. Conclusion Regular follow-up and early diagnosis combined with prompt and intensive treatment may save vision in cases Pseudomonas aeruginosa scleritis following pterygium excision.